The Influence of Nurse Workload on Services Nursing in Class III Inpatient Rooms RSUD Dr. Fauziah Bireuen - Safriani, Safriani; Efendy, Ismail; yuniati, Yuniati (Jurnal Perilaku Kesehatan Terpadu, 2023)
According to the results of a 2018 study conducted by the Indonesian National Nurses Association (PPNI), around 50.9% of nurses working in hospitals report job exhaustion, regular headaches, and are unable to rest because the task is too heavy and time-consuming. A high workload is thought to reduce the occurrence of nursing services in inpatients. The purpose of this study is to investigate the impact of nurse workload on nursing services in inpatient rooms. This is a quantitative approach that employs analytic observational research with a cross-sectional design. The research was carried out at Dr. Fauziah Bireuen Regional General Hospital. The research population consisted of 226 persons, and the sample size was limited to 69 participants using random sampling. At multiple logistic regression 95% confidence level (a=0.05), the data were analyzed using univariate, bivariate using chi-square, and multivariate. Results: Nursing services in Class III Inpatient Room Dr. Fauziah Bireuen Regional General Hospital, influenced by quantitative workload (p=0.000 <0.05) and qualitative workload (p=0.000 <0.05). The most dominant factor affecting nursing services in this study was the qualitative workload variable. Qualitative workload is in the low category, the chance of good nursing services is 37.4 times higher than nurses who receive state the qualitative workload in the high category. In conclusion quantitative and qualitative workloads have an impact on nursing services.